Sudden collapse of a 19th-century masonry structure during its renovation process. (December 2017) - Krentowski, Janusz; Chyzy, Tadeusz; Dunaj, Piotr
Abstract: The investigation and analysis conducted after a catastrophe of a 19th-century masonry structure are presented. During restoration work of a masonry building there was a sudden collapse of the structure, involving parts of a three-storey high outer supporting wall of the building together with the two floors resting on steel beams, as well as the wooden floor of the attic. The modernization works were carried out according to a detailed project documentation. Prior to the beginning of the destruction process there had been no demolition activities going on. Hence, it was essential to determine the actual causes of the collapse as well as to give details concerning the time when the catastrophe occurred. Detailed inventory measurements and non-destructive "in situ" tests, followed by laboratory tests, are described. The tests involved both ceramic materials and lime mortar, as well as steel and wooden parts of the structural elements. Numerical computations of the approximate bearing capacity of the modernized system prior to the catastrophe were performed in a comprehensive way to build a model using the Finite Element Method (FEM). The model employed mostly standard four-node plate-and-disc components of the flat shell type. The computations concerned the static field. Also the effects related to the stability of the structure in terms of large displacements were analyzed. For the computations, an original software was used. As a result of the conducted studies and analyses, it was established and confirmed quantitatively that the main causes of the building disaster were faults made when preparing openings for shop windows in the non-homogeneous structure of the wall. However, the most important issue was flaws of the mortar binding the ceramic elements of the wall. The paper concludes that in the course of wide-ranging restoration of historical facilities, it should be entirely prohibited to treat the building's elements as structural ones. In cases of "limited structural reliability" with respect to the historical facilities, loads should be taken by an independent structure. The modernization works must be carried out under on-going constant supervision of an experienced designer and project manager. The paper ends by presenting a concept of rebuilding of the damaged parts of the facility. Graphical abstract: Highlights: The paper describes collapse of a 19th century masonry structure during its renovation. Inventory measurements, NDT "in situ", as well as laboratory tests have been performed. Numerical computations of the structure prior to the catastrophe are presented. The disaster was caused by faults made while preparing openings for shop windows. The paper closes with a concept of rebuilding the damaged parts of the facility.